When Passion Fades: Disentangling the Temporal Dynamics of Entrepreneurial Passion for Founding - Collewaert, Veroniek; Anseel, Frederik; Crommelinck, Michiel; De Beuckelaer, Alain; Vermeire, Jacob (Journal of Management Studies, 2016)
AbstractThis study examines how and why entrepreneurial passion for founding changes over time. In particular, we propose that in the founding phase of a venture's lifecycle entrepreneurs’ founding identity centrality will remain stable over time. We also propose, however, that in our sample and time period studied, entrepreneurs’ intense positive feelings for founding will decrease over time. On the basis of theories of positive illusion, self‐regulation and role theory, we further hypothesize that venture idea change, change in role ambiguity and entrepreneurs’ feedback‐seeking behaviour are factors that help explain the rate of change in entrepreneurs’ intense positive feelings for founding. Using a three‐wave longitudinal research design, we find that among a sample of 112 entrepreneurs’ identity centrality does not change over time, whereas intense positive feelings for founding decrease over time. Moreover, the more entrepreneurs change their venture ideas, the weaker their decrease in intense positive feelings. Further, we show that entrepreneurs who frequently seek feedback suffer less from reduced positive feelings in response to higher increases in role ambiguity as compared to entrepreneurs who seek less feedback.